Eksplorasi Nilai Budaya Songket Subahnale dan Preferensi Gen Z dalam Pelestarian Budaya Lokal - Qatrunada Qatrunnada; Ni Putu Sinta Dewi (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
This study focuses on the exploration of the Songket Subahnale culture and Generation Z's preferences in preserving local culture, with the aim of understanding how the younger generation can be a bridge between traditional values and the modern world, while ensuring that cultural heritage such as Songket Subahnale remains alive, known, and appreciated across generations. This study uses a qualitative method with a descriptive approach, Data collection techniques are carried out through interviews, participant observation. The results of this study are the tradition of weaving or nyesek in Central Lombok has been carried out for generations, Subahnale songket weaving contains various values that reflect the character of the Lombok community. The craftsmen and the local government have made efforts to preserve it. However, this strategy is still conventional, so it has not fully reached the digital audience, Generation Z's interest in songket can increase if the presentation media is packaged in a more modern and interactive way. A fresher and more innovative visual approach will make songket more easily accepted by the younger generation. The contribution of this study is to provide a model for preserving songket subahnale and recommend a more adaptive and modern design and promotion development strategy through Generation Z's preferences so that it can be carried out by future researchers.